Essays in medieval studies : proceedings of the Illinois Medieval Association - Illinois Medieval Association (Illinois Medieval Association, 1984)
Contents of each vol. selected from papers of the annual meeting of the Illinois Medieval Association.
Keywords: Middle Ages : Congresses; Civilization, Medieval : Congresses; Civilisation médiévale : Congrès : Périodiques; Moyen Âge : Congrès : Périodiques; Middle Ages; Civilization, Medieval; Civilisation médiévale; Moyen Âge